177-Lutecio-DOTATE in the treatment of neuroendocrine rectal tumors with liver metastasis: case report - Abdalla, Mariana Ferrari de Jesus; Santos almeida, Giselle Cristina dos (Brazilian Journal of Oncology, 2020)
The present report describes a case of a neuroendocrine tumor of the rectum with liver metastasis in a 35-year-old woman. The rectum is the second most common location of gastrointestinal neuroendocrine tumors and is typically diagnosed through a screening colonoscopy finding for non-tumor related symptoms. Surgical treatment is indicated when the disease is localized, but, in most cases, this cancer is diagnosed in advanced stages. When advanced stages or metastasis is present, therapeutic include embolization, somatostatin analogs, interventional radiology and radiometabolic peptide therapy. 177-Lutecio-DOTATATE therapy has a positive impact on the quality of life of patients with inoperable metastatic tumors. The case descried was treated with surgery and later with liver segmentectomies, embolization, and octreotide due to liver tumor recurrence. With the persistence of the metastasis, started treatment with 177-Lutecio-DOTATATE. After the second cycle of administration, had partial remission of the tumor and symptoms.
Keywords: Neuroendocrine tumors; Organometallic compounds; Octreotide; Rectal neoplasms